Dukungan keluarga berhubungan dengan motivasi menjalani terapi hemodialisis - Hanifah, Ruth Berlianing; Nurmaguphita, Deasti; Rahayu, Prastiwi Puji (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Chronic kidney disease (CKD) is a condition where kidney function declines irreversibly, resulting in the body's inability to maintain fluid balance, necessitating renal replacement therapy, one of which is hemodialysis. Purpose: To analyze the relationship between family support and the motivation of CKD patients undergoing hemodialysis, to determine the most dominant family support, and to determine the close relationship between family support and motivation for undergoing hemodialysis. Method: This study is a quantitative cross-sectional study. The sampling technique used purposive sampling, calculated using the Slovin formula e = 0.05, for 120 respondents. The family support variable was measured using a family support questionnaire. The motivation variable for undergoing hemodialysis was measured using a hemodialysis motivation questionnaire. Results: The study showed that some CRF patients undergoing hemodialysis were highly motivated, demonstrating their readiness and commitment to undergoing hemodialysis. The most prevalent form of family support was informational support. The analysis revealed a positive correlation with moderate closeness, meaning that the higher the family support received, the higher the patient's motivation to undergo hemodialysis. Conclusion: There is a positive correlation between family support and motivation to undergo hemodialysis. Keywords: Chronic Kidney Failure; Family Support; Hemodialysis; Motivation. Pendahuluan: Gagal ginjal kronik (GGK) adalah kondisi menurunnya fungsi ginjal secara irreversible yang mengakibatkan tubuh tidak dapat mempertahankan keseimbangan cairan, sehingga perlu terapi pengganti ginjal salah satunya hemodialisis. Tujuan: Untuk menganalisis hubungan dukungan keluarga dengan motivasi pasien GGK dalam menjalani hemodialisis, mengetahui dukungan keluarga yang paling dominan, dan bagaimana keeratan hubungan antara dukungan keluarga dengan motivasi menjalani hemodialisis. Metode: Penelitian ini merupakan penelitian kuantitatif dengan pendekatan cross-sectional. Teknik pengambilan sampel dengan metode Purposive Sampling setelah dihitung dengan rumus slovin e = 0,05 sebanyak 120 responden. Variabel dukungan keluarga diukur menggunakan kuesioner dukungan keluarga. Variabel motivasi menjalani hemodialisis diukur dengan kuesioner motivasi menjalani hemodialisis. Hasil: Sebagian pasien GGK yang menjalani hemodialisis memiliki motivasi tinggi, menunjukkan kesiapan serta komitmen pasien dalam menjalani hemodialisis. Dukungan keluarga yang paling dominan diberikan adalah dukungan informasional. Hasil analisis menunjukkan adanya hubungan positif dengan keeratan sedang, yang berarti semakin tinggi dkungan keluarga yang diterima maka semakin tinggi motivasi pasien dalam menjalani hemodialisis. Simpulan : Terdapat hubungan positif antara dukungan keluarga dengan motivasi menjalani hemodialisis. Kata Kunci: Dukungan Keluarga; Gagal Ginjal Kronis; Hemodialisis. Motivasi.